Teníase: Uma causa rara de apendicite aguda - Teixeira, Fábio Vieira [UNESP] (2008)
Acute appendicitis is the most common surgical condition of acute abdomen. Approximately 7 percent of the population will have appendicitis during their lifetime, with the peak incidence occurring between 10 through 30 years-old Obstruction of the appendix lumen with subsequent bacterial infection initiates the pathophysiological sequence of acute appendicitis. Obstruction may have multiple causes, including fecalith, lymphoid hyperplasia (related to viral illnesses, including upper respiratory infection, mononucleosis, and gastroenteritis), foreign bodies, carcinoid tumor and parasites. In Asia, Africa and Latin America, Enterobius vermicularis has been reported as the main parasite that causes appendix obstruction. Rarely, Taenia sp., has been pointed as a cause of parasitic appendicitis. We reported a 30 years-old patient clinically diagnosed with acute appendicitis. The appendectomy was performed through a McBurney incision. The patient's convalescence was uneventful, and he was discharged from hospital 48 hours after operation. Histological examination of the appendix showed acute appendicitis, and it was found aparasite (Taenia sp.) lying inside of the appendix lumen at a transverse section. He has received 10 mg/Kg weight of praziquantel for taeniasis treatment.